2003
DOI: 10.1002/glia.10141
|View full text |Cite
|
Sign up to set email alerts
|

Microglia activation influences dye coupling and Cx43 expression of the astrocytic network

Abstract: Under inflammatory conditions, activated microglia are capable of producing proinflammatory cytokines that are reported to influence cell-to-cell communication. The present study was performed to evaluate the influence of microglial activation on the coupling efficiency of the astroglial network. Primary astrocyte cultures of newborn rats were cocultured with either 5% (M5) or 30% (M30) microglia. Microglial activation (rounded phagocytotic phenotype) was investigated using the monoclonal anti-ED1 antibody, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 54 publications
6
129
1
Order By: Relevance
“…In the experimental brain abscess model which has been developed in our laboratory using S. aureus, we have shown that IL-1β and TNF-α play critical roles in CNS pathology . Interestingly, these same proinflammatory cytokines have recently been reported by others to exert dramatic effects on glial homocellular GJC (Chanson et al, 2001;Duffy et al, 2000;Faustmann et al, 2003;John et al, 1999). Based upon this evidence, we propose that proinflammatory mediators released by S. aureus-activated astrocytes in developing brain abscesses may be capable of modulating the nature and extent of GJC, with changes initiated in the proximity of the lesion and consequently extending to affect the surrounding astrocytic syncytial network.…”
Section: Introductionsupporting
confidence: 75%
“…In the experimental brain abscess model which has been developed in our laboratory using S. aureus, we have shown that IL-1β and TNF-α play critical roles in CNS pathology . Interestingly, these same proinflammatory cytokines have recently been reported by others to exert dramatic effects on glial homocellular GJC (Chanson et al, 2001;Duffy et al, 2000;Faustmann et al, 2003;John et al, 1999). Based upon this evidence, we propose that proinflammatory mediators released by S. aureus-activated astrocytes in developing brain abscesses may be capable of modulating the nature and extent of GJC, with changes initiated in the proximity of the lesion and consequently extending to affect the surrounding astrocytic syncytial network.…”
Section: Introductionsupporting
confidence: 75%
“…A source of IL-1 could be reactive astrocytes as well as activated microglia. In agreement, gap junctional communication between astrocytes is reduced by activated micloglia in cultures [121,42]. These changes in connexin expression may represent reactive gliosis or be part of adaptive processes that reduce damage or provide tolerance to subsequent ischemic episodes (preconditioning).…”
Section: Pattern Of Connexin Expression In the Adult Mammalian Brainmentioning
confidence: 73%
“…A source of IL-1 could be reactive astrocytes as well as activated microglia. Gap junctional communication between astrocytes is reduced by activated microglia in cultures [121,42].…”
Section: Pattern Of Connexin Expression In the Adult Mammalian Brainmentioning
confidence: 99%
“…The levels of soluble factors secreted by microglia following treatment with LPS have been found to be proportional to the numbers of activated microglia cells in vitro (8,25) and in vivo (17,25). Therefore, we studied if the observed increase in the numbers of round microglia in BDVinfected mixed cultures would be associated with an enhanced release of soluble factors following LPS treatment.…”
Section: Fig 2 Lps and Hiv-tat But Not Purified Bdv Activate Microgliamentioning
confidence: 99%